O papel das instituições científicas e tecnológicas (ICTs) nos processos de licenciamento e transferência de tecnologias - Andrade, Antonio Marcos de (2016)
In general, concern for innovation has always been present in the studies of economists. The classical theory was interested more in its effect than its economic causes and Neoclassical gives only secondary to the issue of innovation treatment, expanding the classical concepts. Neoclassical theory saw technology as an exogenous variable, revealing itself unable to explain the change inherent in the process of economic development. Differentiating, these economists, Joseph Schumpeter emphasizes the word "innovation" to feature a number of innovations that can be introduced in the economic system and substantially alter the relations between producers and consumers is a key element for economic development. In his "Theory of Economic Development" (TDE) seeks to distinguish definitions of invention and innovation. For him, innovation is the engine of economic development, that is, through innovation that the business is able to offer new products, better quality products, or reduced costs, allowing you to earn higher profits than other entrepreneurs and thus, the innovative entrepreneur happens to be imitated by other capitalists. And this movement generates a cycle, which is called spectacular economic growth, which is interrupted when the extraordinary profits are diluted among competitors, causing the economy to find a new balance point. The creation of a new technology leads to destruction of the old, this destruction that Schumpeter called "creative destruction." It was from this theory that evolutionary or neo-Schumpeterian current began to see the phenomenon of innovation in the economy for another look, placing it in the center of the investigation. For them, innovation must be seen as the result of a complex and continuous process of experience in the relations between science, technology, research and development in academic institutions, industry and government, only through the interaction of these three actors known as "triple helix" you can create a sustainable and durable innovation system in the era of the knowledge economy. However, the main challenge of Brazilian academic institutions in the twenty-first century is to incorporate innovation and entrepreneurship in teaching, research and extension, aimed at both the training of qualified professionals to market, how to play a role in the system Innovation and economic and technological development. To fulfill this new role, academic institutions had help Innovation Act, 2004. Among various measures, management mechanisms have been developed for scientific and technological institutions and their relationship with the companies. Thus, universities and federal institutes defined by law as an Institution of Science and Technology (ICT) became responsible for structuring an internal organ, called the Center for Technological Innovation (NIT), with the function to manage their innovation policies. Thus, the general objective of this research is to understand how the Technological Innovation Centers-NITs of ICTs (UFS, NIT-IFS and Embrapa Coastal Tablelands) disseminate a culture of innovation, intellectual property and technology transfer. To this end, we sought a methodology of qualitative and descriptive. The survey is divided into five parts: introduction; the second chapter that addressed the economic theories; the third chapter that discussed concepts of innovation, innovation process, licensing and transfer in ICT; the fourth chapter analyzed the results obtained from the questionnaire to NITs (CINTTEC / UFS, NIT / IFS end SPAT / Embrapa Coastal Tablelands) and lastly the final considerations.